Effect of vedolizumab dose intensification on serum drug concentrations and regain of response in inflammatory bowel disease patients with secondary loss of response. Issue 2 (28th February 2021) - Outtier, An; Wauters, Lucas; Rahier, Jean‐Francois; Bossuyt, Peter; Colard, Arnaud; Franchimont, Denis; Lambrecht, Guy; Macken, Elisabeth; Van Moerkercke, Wouter; Baert, Filip; Humblet, Evelien; Van Hootegem, Philippe; et al.
Abstract: Background and Aims: Dose intensification of vedolizumab (VDZ) for moderate‐to‐severe ulcerative colitis (UC) and Crohn's disease (CD) may be effective in patients losing response. We aimed to assess the clinical and pharmacokinetic effect of VDZ dose intensification. Methods: We performed a multicentre open‐label prospective study from June 2017 through December 2018 in patients on VDZ losing response, defined as total Mayo score >6 (UC) or Harvey‐Bradshaw Index >4 with inflammation (CD). Blood samples and clinical scores were collected at baseline and after VDZ infusion at Weeks 4 and 8. Clinical response was defined as a decrease of partial Mayo score ≥2 points or Harvey‐Bradshaw Index ≥3 points. Biological response was defined as a decrease of C‐reactive protein to ≤5 mg/L or of >50%. Results: A total of 59 patients (31 UC and 28 CD) were included. Median (IQR) trough levels (TLs) increased from 8.7 (5.1‐12.7) µg/mL (baseline) to 19.1 (12.4‐22.4) µg/mL (Week 4) and 23.1 (16.7‐28.4) µg/mL (Week 8) (all P < 0.0001). Partial Mayo score decreased with 3 points from baseline to Week 4 ( P = 0.001) but stabilised to Week 8 ( P = 0.16). Harvey‐Bradshaw Index decreased with 4 points from baseline to Week 4 ( P = 0.001) and 1 point to Week 8 ( P = 0.04). Recapture of clinical and biological response was achieved in 49% and 27% at Week 4, and 54% and 37% at Week 8 respectively. Conclusion: Dose escalation to VDZ every 4 weeks after loss of response resulted in higher TLs with regain of clinical response in half of the patients.